A SYSTEMIC REVIEW ON THE FUTURE OF OBSTETRICS AND GYNECOLOGY: HARNESSING ARTIFICIAL INTELLIGENCE. - Sinha, Dr. Varsha (Student’s Journal of Health Research Africa, 2023)
There is a burgeoning interest in the utilization of artificial intelligence (AI) within the realm of medical research, which exhibits considerable potential for forthcoming advancements. Obstetrics and gynecology encompass specialized disciplines that are associated with a heightened susceptibility to legal matters and suboptimal clinical outcomes. Multiple challenges exist in these domains, encompassing the comprehension of fetal physiology and the precise prognostication of prenatal and labor monitoring. The field of gynecology encounters intricacies within the realm of molecular biology, particularly in the comprehension of gynecological malignancies. This review aims to explore the potential applications of AI within the field of obstetrics and gynecology. The present study aims to investigate the potential utility of AI in enhancing comprehension of fundamental principles within various domains, with a particular focus on its potential impact on the healthcare sector. In the realm of obstetrics and gynecology, AI exhibits considerable potential in tackling enduring obstacles and aiding healthcare providers in their decision-making processes.